A BIOGRAPHIC CASE OF BODY DISSATISFACTION - Natalia Solano-Pinto; Félix Díaz-Martínez (Universidade do Estado do Rio de Janeiro, 2016)
In this paper we analyze the life history of a woman, as told in first person by herself and in third person by her partner, focusing on her worries about body image and how they affect various important aspects of her everyday life through the life cycle. Our materials are the respective biographic interviews to a 33-year-old woman and her partner, a 40-year-old man, where they storied her life paying special attention to body image and dissatisfaction issues. The analysis is structured into six emerging themes along both stories: "The gaze of the other and body exposure", "Pregnancy", "Modifying the body", "Socio-cultural pressure", "Masculine desire", and "The silence dilemma". We pay special attention to changes in positioning, feelings and habits with respect to the body along the life cycle, with key moments in teenage, and before, during and after a pregnancy. The analysis of biographies of non-diagnosed persons may help us understand various ways of positioning in the socio-cultural context of Western culture with respect to the body. At the same time, it may facilitate the development of actions to construct a critical view on context, contributing to women's free elaboration of their identity and body experience. DOI: 10.12957/demetra.2016.22473